Holistic Explanation in Architectural Historiography: Inquiry of the Possibility in Response to Branko Mitrovic A Critique on the Book Rage and Denials: Collectivist Philosophy, Politics, and Art Historiography, 1890-1947 - Zeinab Tamassoki; Mehrdad Qayyoomi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This paper attempts to extend Ladislav Kesner and Richard Elbridge's insights toward collectivist explanation in art historiography in response to Branko Mitrovic's critique in Rage and Denials. A counterexample situation in architectural historiography is propounded to elucidate how a collectivist explanation in a moderate realist form is not only apt but, in some cases, inevitable. It relies on our primary claim, the possibility of some non-essentialist, non-ideological, non-deterministic and non-egocentric collectivist explanations, regarding the main faults assigned to collectivist stances in art historiography by Branko Mitrovic. The Counterexample situation explains the possible actions not implemented and decisions not taken in designing a building. In addition to the choices that led to the final formulation of the artwork, one must also consider the other options available, those possible choices that were left out, to clarify feasible limitations and, conversely, the choices that led to the emergence of the work. Even considering that all final decisions merely result from chemical interactions in actors' brains, one cannot judge alternative options the same way, some of which did not even occur in the artist's mind or the network of agents involved. The repetition of dismissing these alternative options during a long-durée, thus the formation of a pattern, cannot be explained by the individualistic stance proposed by Mitrovic.